Cross- Cultural Perspectives of Gender Stereotyping in Homesteads in Bugujju, Mukono - Joshua Amanya (Uganda Christian University, 2024)
The study examined the cross- cultural perspectives of gender stereotyping in homesteads in Bugujju, Mukono. The study was guided by objectives which included; identifying the key social, cultural factors contributing to persistent gender stereotypes in the Bugujju community, examining the influence of prevailing gender stereotypes on the , decision-making, and well-being within the community and investigating the cross cultural perspectives of gender stereotyping within homesteads in the Bugujju region of Mukono. The study was carried out using a cross-sectional research design where both qualitative and quantitative research approaches were also employed. The data were collected using interviews and during the data collection, simple random sampling method was used. A sample size of 60 respondents who were LC1 Chairmen, men, women, girls and boys living in Bugujju was used although 50 of them responded to the study giving a response rate of 83.35. The study findings revealed reveals that while the Bugujju community’s deeply rooted cultural practices play a crucial role in maintaining social cohesion and preserving its heritage, these traditions also impose significant limitations, particularly in terms of gender equity and social mobility. The rigid adherence to traditional gender roles and the perpetuation of stereotypes contribute to social stratification and hinder the potential for economic empowerment and innovation, especially among women and younger generations.
Undergraduate Research